Recruitment and Selection of Honorary Teachers at Senior High School Sungai Aur in West Pasaman Regency: Improving Systems for Educational Excellence - Bilhuda, Asra; Gistituati, Nurhizrah; Nellitawati, Nellitawati; Achyar, Novriyanti (International Journal of Educational Dynamics, 2024)
This study aims to analyze the recruitment and selection processes for honorarium teachers at Senior High School (SHS) Sungai Aur, West Pasaman Regency, with a focus on their alignment with established theories and best practices. Utilizing a qualitative approach, data were collected through direct observations and semi-structured interviews with principals, vice principals, teaching staff, and school committee members. The findings reveal that the current recruitment system does not fully comply with theoretical frameworks. Specific gaps were identified in three critical areas: the socialization of opportunities, the selection process, and the announcement of results. Interviews emphasized the pivotal role of principals and committees in fostering transparent and collaborative communication to align recruitment decisions with institutional goals. However, challenges such as ineffective communication strategies, inconsistencies in candidate evaluations, and a lack of transparency in announcements were found to hinder the effectiveness of the recruitment process. The results highlight the need for a more structured and theory-driven approach to improve the selection and development of competent educators. These findings provide valuable insights into enhancing recruitment frameworks, which are essential for achieving institutional and national educational objectives.